Estimation and Correlation of Clinical Significance of Lipoprotein (a) as a Risk Factor of Atherosclerotic Vascular Events in Elderly: A 1-year Cross-sectional Study in KLE’s Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi - Yashoda Tushar Maladkar; Veerappa Annasaheb Kothiwale (Journal of the Scientific Society)
Introduction: Lipoprotein (a) (Lp(a)) was identified as a variant of low-density lipoprotein (LDL) 40 years ago. Lp(a) consists of one LDL particle containing apoB-100 and one molecule of a large, highly polymorphic glycoprotein known as apo (a). The study aimed to evaluate and correlate the clinical significance of Lp(a) as a risk factor for atherosclerotic vascular events in the elderly population. Materials and Methods: This cross-sectional study was conducted among patients admitted in a tertiary care hospital for for 1 year. One hundred and forty-two study participants included in the study were divided into two groups atherosclerotic vascular event group (2 subgroups: Cardiovascular atherosclerotic vascular event subgroup and neurological atherosclerotic vascular event subgroup) and no atherosclerotic vascular event group. Detailed history, examination, and parameters such as serum Lp(a), serum high-density lipoproteins, LDL, total cholesterol, triglycerides, glycated hemoglobin, and creatinine were tested. Results: Among 142 study participants in the study, majority of study participants were male (n = 96, 67.6%). The mean age was 71.63 years. High Lp(a) levels were noted in 51.41% of study participants. High Lp(a) levels were seen in 56% of study participants in the cardiovascular atherosclerotic vascular event subgroup, 43.33% of study participants in the neurological atherosclerotic vascular event subgroup and 51.61% in no atherosclerotic vascular event group. Conclusion: Our study concludes that Lp(a) may not be used to infer any clinical significance, nor may it have any role to play as a risk factor for atherosclerotic vascular events in the elderly (age >65 years).